2016
DOI: 10.1038/sc.2015.169
|View full text |Cite
|
Sign up to set email alerts
|

How many spinal cord injury patients can catheterize their own bladder? The epidemiology of upper extremity function as it affects bladder management

Abstract: Study design: Retrospective analysis. Objectives: In patients with spinal cord injury, limitations in upper extremity (UE) motor function are cited as a reason for the lack of adherence to clean intermittent catheterization (CIC). By examining the UE function in spinal cord injury (SCI) patients, we aim to provide insight into why CIC 'dropout' occurs and determine a more appropriate target percentage for CIC in this patient population. Setting: United States centers participating in National Spinal Cord Injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 19 publications
3
35
0
Order By: Relevance
“…Although obesity in female patients has been suggested as a barrier to CIC and has been previously linked to the decreased rate of CIC adherence after initial rehabilitation discharge in a study of 665 women with SCI, we did not identify obesity as a variable that impacted satisfaction rates with CIC in the long‐term. This may be due to the lower number of obese women in our cohort (22.2% or 55/193), which limited the power of this subgroup analysis.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Although obesity in female patients has been suggested as a barrier to CIC and has been previously linked to the decreased rate of CIC adherence after initial rehabilitation discharge in a study of 665 women with SCI, we did not identify obesity as a variable that impacted satisfaction rates with CIC in the long‐term. This may be due to the lower number of obese women in our cohort (22.2% or 55/193), which limited the power of this subgroup analysis.…”
Section: Discussionmentioning
confidence: 84%
“…However, population studies have found that only about 50% of patients with SCI use CIC as the primary bladder management method after the initial injury, and 50% of patients with SCI on CIC drop‐out at 5 years of follow up . Female sex, elevated body mass index (BMI), older age, high level of injury/tetraplegia, and impaired upper extremity motor function decreased the odds of bladder management with CIC …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An algorithm previously published by our group was used to characterize the ability to perform CIC on the basis of UE function alone. Specifically, neurologic motor scores for C5 through C8 (involved in the control of UE movement) were transformed and classified as: (a) able to catheterize; (b) possibly able to catheterize; (c) able to catheterize only with reconstructive surgical intervention (eg, catheterizable stoma construction or tendon transfer surgery); and (d) unable to catheterize even with reconstructive surgical intervention (Figure ) …”
Section: Methodsmentioning
confidence: 99%
“…Based on the study by Zlatev et al ,36 it was assumed that 60% of patients perform IC. The total number of prevalent patients with SCI performing IC in Italy was estimated to be about 39 000 (65 000×60%), while the total number of incident patients was about 285.…”
Section: Methodsmentioning
confidence: 99%